Workplace Wellbeing and Employee Engagement on Organizational Citizenship Behaviour Through Work Motivation - Esty, Aulia Widya; Halima, Nur; Winarko, Ruddy (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study aims to analyze the effect of workplace well-being and employee engagement on Organizational Citizenship Behaviour (OCB) through work motivation at PT Pesonna Optima Jasa Jakarta. Workplace well-being is an essential factor that can enhance employee work motivation, ultimately influencing their extra-role behavior within the organization. Employee engagement also plays a crucial role in boosting work motivation, contributing to the creation of a productive and harmonious work environment. This research employs a quantitative method with a survey approach, where data was collected through questionnaires distributed to employees of PT Pesonna Optima Jasa Jakarta. The results indicate that workplace well-being and employee engagement have a positive and significant impact on work motivation. Furthermore, work motivation is proven to be a significant mediator in the relationship between workplace wellbeing and OCB, as well as employee engagement and OCB. These findings affirm that to enhance OCB, companies must focus on improving employee workplace well-being and engagement by fostering work motivation